Data of continuous harvest of stem cells via partial detachment from thermoresponsive nanobrush surfaces - Yeh, Chin Chen; Muduli, Saradaprasan; Peng, I. Chia; Lu, Yi Tung; Ling, Qing Dong; Alarfaj, Abdullah A.; Munusamy, Murugan A.; Subbiah, Suresh Kumar; Murugan, Kadarkarai; Chen, Da Chung; Lee, Hsin Chung; Chang, Yung; et al. (Elsevier, 2016)
This data article contains two figures and one table supporting the research article entitled: “Continuous harvest of stem cells via partial detachment from thermoresponsive nanobrush surface” [1]. The table shows coating conditions of three copolymers, poly(styrene-co-acrylic acid) grafted with oligovitronectin, poly(styrene-co-N-isopropylacrylamide) and poly(styrene-co-polyethylene glycol methacrylate) to prepare thermoresponsive surface. XPS spectra show the nitrogen peak of the polystyrene surface coated with poly(styrene-co-acrylic acid) grafted with oligovitronectin. The surface coating density analyzed from sorption of poly(styrene-co-acrylic acid) grafted with oligovitronectin by UV–vis spectroscopy is also presented.